Unravelling early events in the Taphrina deformans–Prunus persica interaction: an insight into the differential responses in resistant and susceptible genotypes - Svetaz, Laura (2017)
Leaf peach curl is a devastating disease affecting leaves, flowers and fruits, caused by the dimorphic fungus Taphrina deformans. To gain insight into the mechanisms of fungus pathogenesis and plant responses, leaves of a resistant and two susceptible Prunus persica genotypes were inoculated with blastospores (yeast), and the infection was monitored during 120 h post inoculation (h.p.i.). Fungal dimorphism to the filamentous form and induction of reactive oxygen species (ROS), callose synthesis, cell death and defence compound production were observed independently of the genotype. Fungal load significantly decreased after 120 h.p.i. in the resistant genotype, while the pathogen tended to grow in the susceptible genotypes. Metabolic profiling revealed a biphasic re‐programming of plant tissue in susceptible genotypes, with an initial stage co‐incident with the yeast form of the fungus and a second when the hypha is developed. Transcriptional analysis of PRs and plant hormone‐related genes indicated that pathogenesis‐related (PR) proteins are involved in P. persica defence responses against T. deformans and that salicylic acid is induced in the resistant genotype. Conducted experiments allowed the elucidation of common and differential responses in susceptible versus resistant genotypes and thus allow us to construct a picture of early events during T. deformans infection.